2021
DOI: 10.3390/membranes11060436
|View full text |Cite
|
Sign up to set email alerts
|

Composite Anion-Exchange Membrane Fabricated by UV Cross-Linking Vinyl Imidazolium Poly(Phenylene Oxide) with Polyacrylamides and Their Testing for Use in Redox Flow Batteries

Abstract: Composite anion-exchange membranes (AEMs) consisting of a porous substrate and a vinyl imidazolium poly(phenylene oxide) (VIMPPO)/acrylamide copolymer layer were fabricated in a straightforward process, for use in redox flow batteries. The porous substrate was coated with a mixture of VIMPPO and acrylamide monomers, then subsequently exposed to UV irradiation, in order to obtain a radically cured ion-exchange coating. Combining VIMPPO with low-value reagents allowed to significantly reduce the amount of synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Moreover, the progressive swell of a coating when a membrane is placed in a fixed position in a cell may cause crack of the membrane due to the internal stress arisen . Composite hIEMs were previously developed and fabricated with the use of a non-UV-reactive solvent in membrane formulation. , It was proposed that the introduction of a nonreactive solvent to the UV-reactive acrylic precursor mixture allows for the preparation of an ionomer matrix initially swollen by the solvent, limiting the expansion of the coating in contact with water. However, a proper solvent selection for membrane formulation is a challenge since ionomer precursors often reveal drastically different solvation properties.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the progressive swell of a coating when a membrane is placed in a fixed position in a cell may cause crack of the membrane due to the internal stress arisen . Composite hIEMs were previously developed and fabricated with the use of a non-UV-reactive solvent in membrane formulation. , It was proposed that the introduction of a nonreactive solvent to the UV-reactive acrylic precursor mixture allows for the preparation of an ionomer matrix initially swollen by the solvent, limiting the expansion of the coating in contact with water. However, a proper solvent selection for membrane formulation is a challenge since ionomer precursors often reveal drastically different solvation properties.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the usage of AEMs in VRFB applications has attracted great attention because of the low vanadium permeability resulting from the effects of Donnan exclusion on the AEMs cations. , AEMs containing quaternary ammonium, , imidazolium, and pyridinium cations have been investigated for VRFB applications, and those with imidazolium cations have exhibited good performance. …”
Section: Introductionmentioning
confidence: 99%
“… 15 , 16 AEMs containing quaternary ammonium, 15 , 16 imidazolium, 17 and pyridinium 18 cations have been investigated for VRFB applications, and those with imidazolium cations have exhibited good performance. 19 22 …”
Section: Introductionmentioning
confidence: 99%
“…As a critical component, effective anion-exchange membranes (AEMs) are widely used in electrochemical technologies, such as anion-exchange membrane fuel cells (AEMFCs), , flow batteries, , and water electrolysis. , Typically, AEMs are composed of polymer backbones, such as poly­(sulfone)­s, poly­(arylene ether ketone)­s, , and poly­(phenylene oxide)­s, ,, and cationic groups . However, recent studies have shown that the polymer backbone with electron withdrawing groups is chemically unstable under alkaline conditions due to the backbone cleavage resulting from hydroxide ion attack .…”
Section: Introductionmentioning
confidence: 99%
“…As a critical component, effective anion-exchange membranes (AEMs) are widely used in electrochemical technologies, such as anion-exchange membrane fuel cells (AEMFCs), 1,2 flow batteries, 3,4 and water electrolysis. 5,6 Typically, AEMs are composed of polymer backbones, such as poly(sulfone)s, 7 poly(arylene ether ketone)s, 8,9 and poly(phenylene oxide)s, 6,10,11 and cationic groups.…”
Section: Introductionmentioning
confidence: 99%